KEALPAAN SEBAGAI BENTUK KESALAHAN DALAM PIDANA : TELAAH UNSUR SUBYEKTIF DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 1 TAHUN 2023 - Etty Agustin; Tanudjaja Tanudjaja (Journal of Innovation Research and Knowledge, 2026)
Negligence (culpa) is a form of fault in criminal law that plays a crucial role as the basis for criminal liability. The primary challenge in the application of negligence-based offenses lies in proving the subjective element, which is inherently internal and not easily established through conventional evidentiary means. This study aims to analyze the concept of negligence in criminal law and to examine judicial methods for assessing the subjective element of negligence as a key determinant of criminal liability within the framework of Law Number 1 of 2023 concerning the Indonesian Criminal Code. This research employs a normative juridical method with statutory and conceptual approaches. The findings reveal that the 2023 Criminal Code has reinforced the principle of fault as the foundation of punishment; however, judicial practice still shows a tendency to reduce the subjective element of negligence to a purely objective assessment. Therefore, an integrative and layered method of judicial assessment is required to ensure that negligence is proven in an argumentative, contextual, and justice-oriented manner.